Conservation of PcaQ, a transcriptional activator of pca genes for catabolism of phenolic compounds, in Agrobacterium tumefaciens and Rhizobium species. - Parke, D (1996)
In Agrobacterium tumefaciens A348, control of five genes for catabolism of the phenolic compound protocatechuate to beta-ketoadipate is exerted by the gene pcaQ. The product of pcaQ is a transcriptional activator which is distinct from regulators of the beta-ketoadipate pathway characterized in other bacterial groups. An investigation of whether pcaQ is present and conserved in related Rhizobium species employed Southern hybridization and an agrobacterial pcaD::LacZ promoter probe plasmid. These studies revealed that homologs of the activator are widespread among members of the family Rhizobiaceae, being present in Rhizobium leguminosarum, Rhizobium fredii, Rhizobium meliloti, Rhizobium etli, and Rhizobium tropici.